Multiunit Bargaining in Oligopolistic Industries - Davidson, Carl (Journal of Labor Economics, 1988)
A model of wage determination in unionized oligopolistic industries is developed and used to compare the outcome of collective bargaining under two different bargaining structures-one in which the workers of each firm are represented by separate and independent unions (local bargaining) and one in which a national union represents all workers in the industry. In both cases, the bargaining problem has a unique outcome with industrywide bargaining resulting in higher wages. In addition, industrywide unions are inherently stable in that there are no incentives for independent unions to attempt to cheat on the collusive agreement.